"You Were Not There, " The Creation of Humility and Knowledge in Qurʾanic Stories: A Rhetorical and Narratological Analysis. (27th March 2017) - Ozgur Alhassen, Leyla
Abstract : In this study, I explore verses in the Qurʾan that come towards the end of stories and use a second-person address to say, "you were not there" when this happened. I seek to understand what literary function in the story it serves to address the second person and her/ his lack of knowledge, whomever s/he is. I locate all of these verses (3:44, 11:49, 12:102 and 28:44–46) and analyze them in order to obtain a better understanding and analysis of Qurʾanic literary style. I focus on what these stories have in common and how the verses function. In addition, I analyze the verses and their roles in their respective stories. Through this analysis, we see that these verses are generally seen by commentators and modern scholars as asserting the Prophet's authority and the Qurʾan's authenticity. However, I argue that these verses function as a sophisticated Qurʾanic literary and rhetorical device that works to put people in their place: Prophet Muḥammad, his contemporaries, and all of the Qurʾan's audience, by showing them their lack of knowledge and their temporality.